Kyrgyz Republic Public Expenditure Review Policy Notes : Health - World Bank (Washington, DC, 2014)
Over the past two decades the Kyrgyz Republic implemented important health financing and organization reforms. Compared to other former Soviet republics and other low-income countries, the Kyrgyz Republic shows good results in term of health outcomes, access to health services, and financial protection. Life expectancy exceeds that of several of the most prosperous former Soviet republics, including Russia. Infant and under-5 mortality rates were halved between 1990 and 2010. More than 98 percent of births are attended by skilled health staff and children immunization rates exceed 90 percent. Utilization of both hospital and outpatient health services are quite equal across income groups. Overall distribution of public health spending is slightly pro-poor. The Kyrgyz health system shows low incidence of catastrophic and impoverishing out-of pocket spending for health care.